Desenvolvimento de ZrO2/Al2O3 e ZrO2/Al2O3-NbC usando sinterização convencional e não convencional - Salem, Raphael Euclides Prestes (2017)
High performance ceramic composites have been the subject of frequent studies in recent decades, aiming at improving mechanical properties and increasing their range of applications in technological products. This work consisted in studying the preparation, the conventional and non-conventional sintering and the mechanical properties resulting from two t-ZrO2 matrix composites: the t-ZrO2/Al2O3 system and the t-ZrO2/Al2O3-NbC system. In the t-ZrO2/Al2O3 system, the compositions of 0, 5 and 15% by volume of Al2O3 using commercial powders were studied, while in the t-ZrO2/Al2O3-NbC system, an Al2O3-NbC nanocrystalline powder obtained by high energy reactive milling, deagglomerated, leached in HCl and added in the proportion of 5% by volume to the t-ZrO2 matrix. The obtained powders were uniaxially and isostatically pressed and sintered in conventional furnace and using flash sintering (t-ZrO2/Al2O3) and spark plasma sintering (SPS) (t-ZrO2/Al2O3-NbC). Conventionally sintered t-ZrO2/Al2O3 and conventionally sintered t-ZrO2/Al2O3-NbC composites were characterized by measurements of apparent density, dilatometry, SEM, and mechanical properties: hardness, Young's modulus and fracture toughness. The t-ZrO2/Al2O3 composites sintered by FS were characterized by measurements of apparent density, in situ dilatometry and SEM. t-ZrO2/Al2O3-NbC nanocomposites were also characterized for wear strength by the ball-in-disc method, using Al2O3 and WC-6%Co beads as countermaterials. The results showed that the high energy reactive milling was complete and effective in obtaining nanometric powders of Al2O3-NbC, with crystallite sizes equal to 9.1 and 9.7 nm, for Al2O3 and NbC, respectively. The deagglomeration after high energy reactive milling was effective in reducing the size of agglomerates. Conventionally sintered t-ZrO2/Al2O3 and t-ZrO2/Al2O3-NbC composites and SPS-sintered t-ZrO2/Al2O3-NbC showed high densification (> 97% TD), good dispersion of the inclusions in the matrix and good mechanical properties. The t-ZrO2/Al2O3 nanocomposites sintered by FS presented an ultrafast densification (<1 min) with linear shrinkage superior to the sintered samples in conventional furnace, occurring at temperatures lower than 1000°C, with relative densities higher than 90% TD in some compositions. The t-ZrO2/Al2O3-NbC nanocomposites presented competitive properties between conventionally sintered and SPS-sintered composites with higher hardness and fracture toughness than monolithic t-ZrO2. The wear resistance of these conventionally sintered nanocomposites, however, was markedly higher than those of SPS-sintered ones. The oxidation of NbC in the composites sintered conventionally influenced negatively the properties, leading to the suggestion of a "window" of temperatures in which the sintering of the t-ZrO2/Al2O3-NbC nanocomposite is interesting without the degradation of the mechanical properties. The results allowed concluding that the studied materials present potential for industrial applications that require high mechanical performance and wear resistance ceramics.